Aplikasi Sistem Administrasi Percetakan Digital pada Toko Pelangi di Ambon - Riandro Setiyo Louryanto; Lily Puspa Dewi; Alexander Setiawan (Jurnal Infra, 2019)
Pelangi Shop is a shop that sells photography products, photo shooting service provider as well as a supplier of photo and banner printing services. Pelangi shop is located in a strategic place, which is at the center and middle of Ambon city. However, Pelangi Shop's business operational system is still done manually, so there can be several problems such as lack of control over the incoming and outgoing stock of the goods.Seeing the problems and conditions of the Pelangi Shop above, Pelangi Shop needs an administrative system application to assist the business operations. In addition, this administration system application makes it easier for stores to marketing the products and make it easier for stores to manage incoming orders. And also can facilitate the store to confirm orders for customers.The results obtained from this application include recording the master of goods, recording in and out transactions of goods and stock cards with the average calculation method, recording incoming orders and managing customer order status and checking proof of transfer payment from customers, as well as reports such as reports on purchased goods and sales of goods.